Subtle subversions: resisting colonialism through religion - Simmons, Caleb (Religion, 2020)
Each focusing on a different geographical region and time period, the articles in this volume examine the different ways that colonised peoples used religious expression to subtly subvert colonial power. We call these types of resistance subtle' to contrast them with the forms of colonial resistance that were more apparent to the colonisers, such as military conflict and vocal protest movements, while being readily apparent to the indigenous peoples who utilised them.